ICBC and Standard Bank : growing global - Williamson, Peter J., (SAGE knowledge. Cases., 2016)
This case examines the globalisation process of ICBC, one of China's leading banks. Specifically, it explores the path-breaking US$5.46 billion acquisition in 2008 of a 20% shareholding in Standard Bank based in South Africa and the associated strategic partnership between the two banks to develop their global business.